Chilhood pleural tuberculosis in a region of high prevalence of tuberculosis: A review of 96 cases - Reto Valiente , Luz (2013)
Study objective: To describe the clinical features, radiographics, laboratory and bacteriologic findings of pediatric patients with tuberculous pleural effusion. Material and Methods: It is a retrospective study. We have collected information from medical records of inpatients < 16 years old, who were admitted at Hipolito Unanue Hospital from January 2003 to December 2012, with diagnosis of tuberculous pleuritis. Results: Ninety – six children were diagnosed with tuberculous pleural effusion. The median age was 11 years. 60.42% of the patients were eutrophic, 26.04%were overweight or obese and only 13.65%suffered of malnutrition. Positive tuberculin skin tests were seen in 89.86%. Pleural effusion was the sole radiographic manifestation in 36.5% of cases and parenchymal disease was associated in 63.5% of the patients. Bacteriologic confirmation of tuberculosis was achieved in 13 cases (13.5%). Antituberculous therapy for 6 months was effective in all cases. Conclusions: Tuberculous pleural effusion was usually associated with a positive tuberculin skin test, and lung parenquimal infiltrates. A short course of chemotherapy is effective.